A revision of the southern African katydid genus Griffiniana Karny (Orthoptera: Tettigoniidae: Mecopodinae) - Naskrecki, Piotr; Bazelet, Corinna S. (Zootaxa, 2012)
The South African genus Griffiniana Karny of squamipterous to macropterous katydids (Tettigoniidae: Mecopodinae:Aprosphylini) is revised and a key to species is provided; G. duplessisae sp. n. from the Western Cape Province is de-scribed; acoustic behavior of G. capensis Karny, G. duplessisae, and G. longipes (Naskrecki) is described. The genusEwanella Naskrecki is considered a junior synonym of Griffiniana, and E. breviuscula Gorochov is synonymized with G. longipes.